Being ‘excluded from the world of sound’: Deafness, Invalidism and Resilience in Harriet Martineau’s Writings (1834–1855) - Manuela D’Amore (Cahiers Victoriens et Edouardiens)
Centred on the Victorian intellectual Harriet Martineau (1802-76), this paper will show how she lived her condition as a deaf person and an ‘invalid’. Detailed information about her memories of the ‘world of sound’—also the impact that deafness had on her life—can be found in her hybrid prose. Blending different genres and text forms, Letter to the Deaf (1834), the journal article ‘Deaf Mutes’ (1854) and her two-volume Autobiography (1855–1877) are clear on her determination to use her most painful experiences to promote social change. In fact, she immediately started from the feelings that she associated with the pleasures of sound and music. Before she lost her hearing as a young adolescent, she enjoyed singing and ‘was never out of tune’: it was only after she became fully aware of her disability that she urged her ‘fellow sufferers’ to trust even experimental science to gain ‘every breath of sound’ and play an active role in the public sphere. An eclectic and prolific writer, Harriet Martineau contributed to a thorough rediscussion of the nineteenth-century cult of invalidism in England. Even today her works show how she challenged Victorian convictions on deafness and traditional medical practices, while laying the basis for a more equal and inclusive society.